2005
DOI: 10.1038/ja.2005.69
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid Inhibits Syncytium Formation Accompanied by Reduction of gp120 Expression

Abstract: Mycophenolic acid (MPA) was identified as an inhibitor of syncytium formation during the screening of human immunodeficiency virus (HIV) entry inhibitors. MPA is a well-known inhibitor of inosine monophosphate dehydrogenase and anti-HIV activity has been reported in vitro and in vivo. MPA inhibited syncytium formation in T cell-tropic and macrophage-tropic systems with IC 50 values of 0.1 and 0.5 m M, respectively. The reduction of HIV gp120 expression by MPA (1.0 mM) was observed by use of Western blot analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…MPA is known to be active against HIV especially in combination with abacavir (64,65). The mechanism of anti-HIV activity is believed to be secondary to guanosine triphosphate depletion, with the inhibition of reverse transcriptase, and also through a reduction in gp120 expression in transformed cells (66). Several studies suggested that MPA may have a role in the treatment of multidrug-resistant HIV infection; however, clinical trials have failed to show a signi¢cant bene¢t from the addition of MMF to anti-retroviral regimens.…”
Section: Table1mentioning
confidence: 99%
“…MPA is known to be active against HIV especially in combination with abacavir (64,65). The mechanism of anti-HIV activity is believed to be secondary to guanosine triphosphate depletion, with the inhibition of reverse transcriptase, and also through a reduction in gp120 expression in transformed cells (66). Several studies suggested that MPA may have a role in the treatment of multidrug-resistant HIV infection; however, clinical trials have failed to show a signi¢cant bene¢t from the addition of MMF to anti-retroviral regimens.…”
Section: Table1mentioning
confidence: 99%
“…13 Since its rst report, MPA and its derivatives have been hot research topics due to their vast array of bioactivities ranging from antibacterial, antifungal, antiviral, antitumor to immunosuppressive aspects. [14][15][16][17] Mycophenolate mofetil (MMF), a 2-morpholinoethyl ester prodrug of MPA, is a potent inhibitor of inosine-5 0 -monophosphate dehydrogenase (IMPDH) that is a crucial rate-limiting enzyme in the purine metabolic pathway. IMPDH inuences numerous cellular processes such as replication, transcription and signaling.…”
Section: Introductionmentioning
confidence: 99%